Vern's / Nurul Shazwani Binti Mohd Shukri ... [et.al.]. - Mohd Shukri, Nurul Shazwani; Sulaiman, Nur Ain; Edmund, Joceyline Tubong; Mohamad Ghauzi, Ghasha Farisha; Sobri, Shifaa Afiqah (2019)
Vern's outlet is one of the shoe stores that can be found in Malaysia. However, one of the Vern's outlet can be find in The Summer Mall of Kota Samarahan. As the Kota Samarahan can be called as a district area, the developer of The Summer Mall, Tetap Majumas Sdn Bhd has create a big shopping complex for the people in the Kota Samarahan. Other than the people who lived in the Kota Samarahan, we would like to grab the attention of the people to go for a shop at the Vern's outlet.